GASTRIC VOLVULUS - MUKDEEPROM, Panida (The ASEAN Journal of Radiology, 2023)
Gastric volvulus is a rare but important cause of high intestinal obstruction. Three cases of gastric volvulus were presented, one organoaxial and two mesenteroaxial vol- vulus. Radiographic findings in these three cases were typical. It is essential that the radiologists recognize the radiographic features of gastric volvulus since prompt cor- rective surgery is vital in proper management of these patients. Gastric volvulus is a rare condition defined as an abnormal anterior or posterior rotation of part or all of the stomach about either the saggital or coronal plane of the gastric body. The two main types of volvulus are the organoaxial volvulus - the stomach is twisted around its long axis or coronal plane - and the mesenteroaxial Volvulus where the stomach is twisted around the axis joining the lesser and greater curvature (saggital plane). Volvulus can be complete or partial and can occur in the abdomen or be intratho- racic. The diagnosis of this category can be made by plain film and contrast study of the gastrointestinal tract.